Eating Behavior in Children Aged 3–6: Relationship With the Child's Temperament Characteristics and Parent's Feeding Style - İbrahim Zeyrek; Esra Güney; Ahmet Özaslan; Asiye Uğraş Dikmen (Brain and Behavior)
ABSTRACT Objective To explore the relationship between children's eating behaviors, parental feeding behaviors, and child temperament among Turkish preschoolers aged 3–6 years. Methods A cross‐sectional survey study was conducted between September 2021 and January 2022. Participants included 203 parents of preschool‐aged children (aged 3–6 years) attending nursery and kindergartens, as well as those seeking help from the Department of Child and Adolescent Psychiatry. Analyses were performed utilizing IBM SPSS Statistics version 23.0. Categorical variables are summarized in tables, showing counts and percentages in the descriptive statistics section. The association between continuous variables was assessed through Spearman correlation analysis. In this study, a significance level of p < 0.05 was established. Results Emotional feeding was positively associated with emotional overeating and a desire to drink in children (r = 0.316, p < 0.01; r = 0.266, p < 0.01). Emotional overeating correlated negatively with instrumental feeding (r = −0.158, p < 0.05) but positively with encouragement feeding (r = 0.215, p < 0.01). The temperamental trait of surgency was positively associated with the desire to drink (r = 0.177, p < 0.05) and satiety responsiveness (r = 0.226, p < 0.01). Negative affect correlated negatively with enjoyment of food (r = −0.255, p < 0.01) and food fussiness (r = −0.225, p < 0.01) but positively with satiety responsiveness (r = 0.347, p < 0.01) and slowness in eating (r = 0.282, p < 0.01). Effortful control exhibited negative associations with emotional overeating (r = −0.207, p < 0.01) and the desire to drink (r = −0.141, p < 0.05). Conclusions This study identifies significant associations between specific parental feeding behaviors and children's eating habits, along with the influence of child temperament traits on these behaviors. Key findings highlight the positive relationship between emotional feeding and children's emotional overeating, along with the significant negative impacts of effortful control on emotional overeating and the desire to drink. Other noteworthy results include the strong negative association between negative affect and enjoyment of food, as well as its positive correlation with satiety responsiveness and slowness in eating. These results suggest that both parental feeding strategies and individual temperamental traits significantly influence preschoolers’ eating behaviors. Interventions tailored to enhance parental feeding styles while considering children's temperaments may promote healthier eating practices in young children.